The assessment of factors affecting the perception of comfort and discomfort in dialyzed patients with the use of Katharine Kolcaba’s theory - Grochans, Elżbieta; Schneider, Daria; Szkup-Jabłońska, Małgorzata; Kuczyńska, Magdalena; Jurczak, Anna; Grzywacz, Anna; Mroczek, Bożena; Karakiewicz, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. The comfort of life in dialyzed patients may be considerably lowered. The assessment of its level was based on Katharine Kolcaby’s Theory of Comfort. Aim of the study. The aim of this study was to assess factors which affect the feeling of comfort or discomfort in dialyzed patients. Material and methods. The study involved 95 patients dialyzed in dialysis centres in Szczecin. Some 54% of respondents were women and 46% — men. The average age was slightly more than 54 years, and the range of age was between 18 and above 80. The study was based on a diagnostic survey performed using the General Comfort Questionnaire (GCQ) for measuring the holistic comfort divided into physical, psychospiritual, sociocultural, and environmental aspects. Results. Satisfactory level of comfort was noted in all aspects, namely the environmental aspect — 68.2%, psychospiritual aspect — 66.08%, sociocultural aspect — 54.96%, and the physical aspect — 54%. The score of general comfort level was 3.04 points (60.80%). Conclusions. 1. Implementation of nursing intervention in the physical and social aspects may significantly improve the level of comfort of dialyzed patients. 2. The knowledge of patients’ needs and expectations is necessary to plan nursing care and the main source of such knowledge is regular research on comfort levels in dialyzed patients.